The Evolution of Mako Brimob Kelapa Dua Depok Strategy in Security Ahead of the 2024 Elections from the Threat of Terrorism - Ilham Dewangga Saputra; Sapto Priyanto (Asian Journal of Social and Humanities, 2023)
Indonesia is a democratic country where general elections serve as a fundamental pillar in realizing democratic principles and act as a crucial mechanism ensuring active citizen participation in determining their representatives. Given the significance of the election moment as a pivotal point in Indonesia's political dynamics, it brings about a vulnerable risk of security disturbances, including terrorism threats. Indonesia bears a significant presence of terrorism, ranking third in the Asia-Pacific region according to the Global Terrorism Index 2023. The aim of this research is to elucidate the evolution of security strategies implemented by Mako Brimob Kelapa Dua Depok in facing terrorism threats related to the 2024 elections. The research method employed is qualitative, utilizing theories of security intelligence, social construction, and terrorism concepts. The results indicate that the 2024 General Election in Indonesia is a crucial political event, with a primary focus on anticipating terrorism threats due to the perceived intense political dynamics, increased political polarization, fierce competition among political parties, and extensive use of social media. Forms of terrorism leading up to the election include physical attacks, cyber-attacks, voter intimidation, and potential political conflicts. Security intelligence strategies in facing terrorism have evolved to involve prevention, intervention, and recovery. Strategic steps include establishing specialized intelligence agencies, technological advancements, and inter-agency collaboration. The evolution of security strategies related to the 2024 elections encompasses increased intelligence activities, enhanced intervention capabilities, and preparation for post-terrorism recovery. Special task forces, specialized equipment procurement, and collaboration with various stakeholders demonstrate Mako Brimob's efforts to enhance responses to terrorism threats